2012
DOI: 10.1002/lsm.22022
|View full text |Cite
|
Sign up to set email alerts
|

Indocyanine green‐augmented diode laser therapy of telangiectatic leg veins: A randomized controlled proof‐of‐concept trial

Abstract: ICG-augmented diode laser therapy has proved to be a safe and effective treatment option for telangiectatic leg veins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 34 publications
0
15
0
4
Order By: Relevance
“…If the vessel was still visible after the first DL pulse, a second pulse was applied at the same site (double pulse). Double pulses and radiant exposures of 60–110 J cm −2 were shown to be efficacious and safe in our pilot trial . At 808 nm there is nearly no absorption of radiation in water, but the absorbing chromophore (ICG) is located exclusively within the vessel.…”
Section: Methodsmentioning
confidence: 80%
See 2 more Smart Citations
“…If the vessel was still visible after the first DL pulse, a second pulse was applied at the same site (double pulse). Double pulses and radiant exposures of 60–110 J cm −2 were shown to be efficacious and safe in our pilot trial . At 808 nm there is nearly no absorption of radiation in water, but the absorbing chromophore (ICG) is located exclusively within the vessel.…”
Section: Methodsmentioning
confidence: 80%
“…The vessel temperature was up to 45 °C higher when ICG was added at a dose of 1 or 2 mg kg −1 prior to laser irradiation . We have recently shown that ICG+DL therapy may be a new treatment option for capillary malformations and TLV . Based on these investigations, we compared the impact of ICG+DL therapy at a total dose of 4 mg kg −1 with the standard treatment, Nd:YAG laser therapy, in 29 participants with TLV in a randomized controlled clinical trial.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Diese Ergebnisse konnten in einer weiteren Anwendung durch mathematische Modellberechnungen bestätigt werden [35]. Die klinische Etablierung der ICG-augmentierten Lasertherapie gelang weltweit erstmalig im letzten Jahr in der Regensburger Hautklinik im Rahmen zweier "investigator initiated trials" [58,59]. Im Rahmen dieser randomisierten, kontrollierten klinischen Studien wurden Patienten mit Feuermalen (n = 31) und Besenreisern (n = 15) erfolgreich mittels ICG-augmentierter Diodenlasertherapie behandelt.…”
Section: Vaskuläre Läsionenunclassified
“…Unerwünschte Arzneimittelwirkungen im Rahmen der ICGApplikation traten nicht auf. Lokale Komplikationen wie Wundheilungsstörungen, Blasen-oder Krustenbildung, Pigmentverschiebungen oder Narbenbildung zeigten sich lediglich in einem Fall in Form eines Närbchens [58,59].…”
Section: Vaskuläre Läsionenunclassified